Deniquelata barringtoniae gen. et sp. nov., associated with leaf spots of Barringtonia asiatica - Ariyawansa, Hiran A.; Maharachchikumbura, Sajeewa S.n.; C.karunarathne, Samantha; Chukeatirote, Ekachai; Bahkali, Ali H.; Kang, Ji-Chuan; Bhat, Jayarama D.; Hyde, Kevin D.. (Phytotaxa, 2013)
Deniquelata barringtoniae gen. et sp. nov. (Montagnulaceae) forms numerous ascomata on distinct zonate leaf spots of Barringtonia asiatica (Lecythidaceae). We isolated this taxon and sequenced the 18S and 28S nrDNA. The result of phylogenetic analysis based on 18S and 28S nrDNA sequence data indicate that the genus belongs in the family Montagnulaceae, Dothideomycetes, Ascomycota. The ascomata are immersed, dark brown to black, with bitunicate asci and brown, muriform ascospores. Deniquelata is distinguished from the other genera in Montagnulaceae based on its short, broad, furcate and pedicellate asci, verruculose ascospores with short narrow pseudoparaphyses with parasitic naturee and this is also supported by molecular data. A new genus and species is therefore introduced to accommodate this taxon. We used isolates of this species to show via pathogenicity testing that the taxon is able to cause leaf spots when leaves are pin pricked.